Horton hatches the egg - Geisel, Theodor Seuss Dr. 1904-1991 (New York Random House, 1968)
When a lazy bird hatching an egg wants a vacation, she asks Horton, the elephant, to sit on her egg--which he does through all sorts of hazards until he is rewarded for doing what he said he would.
b
H
Keywords: Elephants -- Juvenile fiction; Fantasy; Stories in rhyme